Mechanisms Underlying Organizational Citizenship Behavior: Linking Responsible Leadership, Organizational Justice, and Proactive Personality Through Job Satisfaction and Affective Commitment - Wahyu Gumilang; Harits Hijrah Wicaksana (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the mechanisms underlying Organizational Citizenship Behavior by integrating the roles of Responsible Leadership, Organizational Justice, and Proactive Personality, while positioning Job Satisfaction and Affective Commitment as mediating variables. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through a survey of 396 employees in the packaging industry located in Serang Regency, all of whom had a minimum tenure of one year. The results indicate that Organizational Justice and Proactive Personality have a positive and significant effect on OCB, whereas Responsible Leadership does not exhibit a significant influence. Mediation analysis reveals that Job Satisfaction plays a significant mediating role in the relationship between Proactive Personality and OCB, while Affective Commitment is not supported as a mediating variable. Furthermore, Proactive Personality shows a strong influence on both Job Satisfaction and Affective Commitment; however, only Job Satisfaction directly contributes to the enhancement of OCB. Overall, the findings underscore the importance of fair and satisfying work experiences in fostering OCB and provide practical implications for human resource management in the packaging industry.